2017 IEEE International Conference on Communications Workshops (ICC Workshops) 2017
DOI: 10.1109/iccw.2017.7962662
|View full text |Cite
|
Sign up to set email alerts
|

Indoor office wideband penetration loss measurements at 73 GHz

Abstract: This paper presents millimeter wave (mmWave) penetration loss measurements and analysis at 73 GHz using a wideband sliding correlator channel sounder in an indoor office environment. Penetration loss was measured using a carefully controlled measurement setup for many common indoor building materials such as glass doors, glass windows, closet doors, steel doors, and whiteboard writing walls. Measurements were conducted using narrowbeam transmitter (TX) and receiver (RX) horn antennas that were boresight-aligne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…Indoor and outdoor environments at D-band and THz frequencies need to be extensively investigated for the impact of penetration loss of common materials, as knowledge of such loss shall be essential to predict indoor and outdoor-to-indoor path loss needed for the design and installation of future 5G mmWave wireless systems in and around buildings [7], [44]. Penetration measurements at 140 GHz were conducted at the NYU WIRELESS research center, where T-R separation distances of 3, 4, and 5 m were used and the TX/RX antenna heights were 1.5 m (see Fig.…”
Section: Free Space Path Loss and Indoor Penetrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indoor and outdoor environments at D-band and THz frequencies need to be extensively investigated for the impact of penetration loss of common materials, as knowledge of such loss shall be essential to predict indoor and outdoor-to-indoor path loss needed for the design and installation of future 5G mmWave wireless systems in and around buildings [7], [44]. Penetration measurements at 140 GHz were conducted at the NYU WIRELESS research center, where T-R separation distances of 3, 4, and 5 m were used and the TX/RX antenna heights were 1.5 m (see Fig.…”
Section: Free Space Path Loss and Indoor Penetrationmentioning
confidence: 99%
“…Fig. 5 shows an example of the penetration loss measurements with the 140 GHz channel sounder for different common materials, with results given in Table II. TABLE II: Comparison of drywall and clear glass penetration loss at 28, 73, and 140 GHz [44], [45] Frequency (GHz) MUT Thickness (cm) Penetration Loss (dB) Avg. Penetration Loss (dB/cm) 28 [1], [45] Clear glass A 1.2 3.6 3.0 28 [1], [45] Clear glass B 1.2 3.9 3.25 28 [1], [45] Drywall A 38.…”
Section: Free Space Path Loss and Indoor Penetrationmentioning
confidence: 99%
“…To determine the received power P r (d) at a distance d, we recorded the power of the first-arriving multipath component (MPC) from the observed power delay profiles [14]- [16], because the first-arriving path was supposed to be a penetration path. We paid no attention to later-arriving paths as they considered to come from reflections caused by nearby obstacles in the environment [17].…”
Section: Measurement Methodologymentioning
confidence: 99%
“…The results in [13] showed that at 60 GHz due to large penetration and pathloss the signal can be effectively confined to a single room. Additionally, Rappaport et al observed that penetration loss at 73 GHz does not necessarily increase and decrease based on the antenna polarization configuration [14]. In [14] a measurement campaign was also performed in a typical indoor office environment at 73 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, multiple wireless channel sounding campaigns have been presented in the literature for access environments above 3GHz, for example, at 5. [1,5,[23][24][25][26], 60 GHz and 70 GHz [16,[27][28][29][30], 83.5 GHz [31], and 110 GHz [32].…”
Section: Introductionmentioning
confidence: 99%